Total laparoscopic partial hepatectomy versus open partial hepatectomy for primary left-sided hepatolithiasis: study protocol for a randomized controlled trial - Shu-bo Pan; Chun-li Wu; Da-chen Zhou; Qi-ru Xiong; Xiao-ping Geng; Hui Hou (Trials, 2024)
Abstract Background The advantages of laparoscopic left-sided hepatectomy (LLH) for treating hepatolithiasis in terms of the time to postoperative length of hospital stay (LOS), morbidity, long-term abdominal wall hernias, hospital costs, residual stone rate, and recurrence of calculus have not been confirmed by a randomized controlled trial. The aim of this trial is to compare the safety and effectiveness of LLH with open left-sided hepatectomy (OLH) for the treatment of hepatolithiasis. Methods Patients with hepatolithiasis eligible for left-sided hepatectomy will be recruited. The experimental design will produce two randomized arms (laparoscopic and open hepatectomy) at a 1:1 ratio and a prospective registry. All patients will undergo surgery in the setting of an enhanced recovery after surgery (ERAS) programme. The prospective registry will be based on patients who cannot be randomized because of the explicit treatment preference of the patient or surgeon or because of ineligibility (not meeting the inclusion and exclusion criteria) for randomization in this trial. The primary outcome is the LOS. The secondary outcomes are percentage readmission, morbidity, mortality, hospital costs, long-term incidence of incisional hernias, residual stone rate, and recurrence of calculus. It will be assumed that, in patients undergoing LLH, the length of hospital stay will be reduced by 1 day. A sample size of 86 patients in each randomization arm has been calculated as sufficient to detect a 1-day reduction in LOS [90% power and α = 0.05 (two-tailed)]. The trial is a randomized controlled trial that will provide evidence for the merits of laparoscopic surgery in patients undergoing liver resection within an ERAS programme. Conclusions Although the outcomes of LLH have been proven to be comparable to those of OLH in retrospective studies, the use of LLH remains restricted, partly due to the lack of short- and long-term informative RCTs pertaining to patients with hepatolithiasis in ERAS programmes. To evaluate the surgical and long-term outcomes of LLH, we will perform a prospective RCT to compare LLH with OLH for hepatolithiasis within an ERAS programme. Trial registration ClinicalTrials.gov NCT03958825. Registered on 21 May 2019.